Instrumental Autonomy, Political Socialization, and Citizenship Identity A Case Study of Korean Minority Citizenship Identity, Bilingual Education and Modern Media Life in the Post-Communism Transitioning China / by Mengyan (Yolanda) Yu. - Yu, Mengyan (Yolanda). (Governance and Citizenship in Asia, 2017)
This book offers essential insights into Chinese Korean minority youth citizenship identity development during their high school and university education period out of their political socialization experience. It investigates how they develop their citizenship identity with the state through bilingual education and media exposure, as an outcome of the entangled relationship between state power and economic globalization. The book demonstrates to readers how to apply the abstract conceptual framework of identity politics and ideology construction, nurtured by both civil culture and political evolvement, to a specific case with operationalized measurement extracted from political socialization concepts so as to understand and rationalize identity development. This approach offers both an in-depth way to penetrate further in the discourse construction that shapes identity politics and an innovative means of measuring and explaining relevant relationships.